Targeting GluN2B/NO Pathway Ameliorates Social Isolation–Induced Exacerbated Attack Behavior in Mice - Fang, Weiqing; Wang, Xiaorong; Cai, Miao; Liu, Xinxin; Wang, Xuemeng; Lu, Wen (Frontiers in Pharmacology, 2021)
Exacerbated attack behavior has a profound socioeconomic impact and devastating social consequences, however, there is no satisfactory clinical management available for escalated attack behavior. Social isolation (SI) is widespread during this pandemic and may exert detrimental effects on mental health, such as causing heightened attack behavior. To explore the therapeutic approaches that alleviate SI-induced heightened attack behavior, we utilized pharmacological methods targeting the GluN2B/NO signaling pathway during the attack behavior. Ifenprodil and TAT-9C peptide targeting GluN2B showed that the inhibition of GluN2B mitigated SI-induced escalated attack behavior and SI-induced aberrant NO level in the brain. Additionally, the potentiation of NO level by L-arginine reversed the effects of the inhibition of GluN2B. Moreover, we showed that high doses of L-NAME and 7-NI and, sub-effective doses of L-NAME in combination with ifenprodil or TAT-9C or sub-effective doses of 7-NI plus ifenprodil or TAT-9C, all decreased SI-induced escalated attack behavior and reduced the NO level, further supporting the idea that GluN2B/NO signaling is a crucial modulator of the escalated attack behavior.